Kilohertz-Linewidth Brillouin Photonic Crystal Fiber Laser With Non-Resonance Pumping Configuration - Guoqing Ji; Zhiyuan Huang; Wenbin He; Ruochen Yin; Yu Zheng; Xin Jiang; Yuxin Leng; Meng Pang (IEEE Photonics Journal)
Brillouin fiber laser with the non-resonance pumping configuration, has compact set-up, good wavelength tunability and high-power single-frequency-emission capability, being regarded as an important technique for highly-coherent light generation. Such Brillouin fiber lasers, using single-mode fiber (SMF) as the Brillouin gain medium, generally have high lasing thresholds and mode-hopping instabilities, resulting from the relatively-low Brillouin gain coefficient of the conventional SMF. Here, we report a compact, non-resonance-pumping Brillouin photonic crystal fiber laser that can generate kHz-level-linewidth single-frequency lasing with tens-of-mW lasing threshold. Mode-hopping instability of this laser is largely suppressed thanks to the short (∼20 m) cavity length, which gives rise to a free-spectral-range (FSR) value of ∼10 MHz properly matching the tens-of-MHz Brillouin gain bandwidth. Experimental results of both self-heterodyne and frequency-noise measurements indicate a laser linewidth of ∼1.4 kHz, corresponding to high linewidth-narrowing ratio of ∼18. No lasing line of high-order Stokes was observed in experiments as the laser pump power was gradually increased to ∼200 mW, giving a nearly-linear lasing slope.